New Chinese Bible Translations and Decolonialism/Postcolonialism in the Progress of the Sinicization of Christianity - FENG, Jacob Chengwei (Journal of Research for Christianity in China (JRCC), 2025)
This paper aims to study the Chinese Bible translations from the second half of the 20th century to the present, with the sinicization of Christianity as the historical and cultural backdrop for the efforts to produce new translations of the Bible. The paper suggests that new translations of the Bible should engage in a fruitful dialogue with the global decolonialism/postcolonialism in academia. The paper analyzes the complete Chinese versions of the Bible translated by Chinese translators, namely the Chinese Contemporary Bible (1979, 当代圣经译本), Modern Chinese Translation (1979, 现代中文译本), Today’s Chinese Version (1993, 圣经新译本), The Recovery Version Bible (2005，圣经恢复本), Chinese New Living Translation (2012, 新普及译本), and the Worldwide Bible Translation (2023, 环球圣经译本). This paper argues that, based on an analysis of the biblical texts and the funding behind the translations, among the seven translations, the Recovery Version and the Worldwide Bible Translation practically embody the concept of the sinicization of Christianity while balancing it with de/postcolonialism within the Chinese context.
Keywords: sinicization of Christianity; Chinese Bible translation; postcolonialism; decolonialism